Determination and comparison of solutions importance and approaches contribute to waste minimization among manufacturing firms in Shah Alam, Malaysia - Mallak, Shadi Kafi; Ishak, Mohd Bakri; Mohamad Kasim, Mohamad Roslan; Abu Samah, Mohd Armi (IDOSI, 2015)
Waste minimization plays an important role in sustainable industrial waste management. It is the most effective method in controlling waste arising. There are some common factors contribute in effective practicing of waste minimization in both developing and developed countries. This study examines and compares the most important solutions and approaches in enhancement of practicing waste minimization among 214 manufacturing industries in Shah Alam, Malaysia. Quantitative data were analyzed using both descriptive and inferential statistics. It was revealed that improvement in internal monitoring system has the higher effectiveness in practicing waste minimization among other factors (SI=67.40%). Also respondent‘s perception toward approaches regarding awareness, encouragement and cooperation were found significantly higher than other approaches (p<0.05). The findings of this study highlight the necessity of training programs and technology modification as well as improvement in monitoring systems.